Hypersensitivity Pneumonitis with Normal High Resolution Computed Tomography Scans - Farah J Nasser-Sharif; Meyer S Balter (Canadian Respiratory Journal)
A case of symptomatic hypersensitivity pneumonitis with normal high resolution computed tomography (CT) scans is presented. The patient, a 32-year-old man with systemic lupus erythematosus, had a chronic, progressive history of respiratory symptoms, abnormal findings on examination and abnormal pulmonary function tests but normal high resolution CT scans of the chest. Diagnosis was made through open lung biopsy. Clinical improvement was seen on removal of the offending antigen. The literature on the utility of high resolution CT scans in hypersensitivity pneumonitis is reviewed.